2016
DOI: 10.3109/09638288.2015.1107774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression following a stroke on the participation component of the International Classification of Functioning, Disability and Health

Abstract: Depression is a moderate predictor of participation among stroke survivors, explaining 51% of the decline of this aspect. Thus, depression should be diagnosed, monitored and treated to ensure a better prognosis regarding social participation following a stroke. Implications for Rehabilitation Individuals with post-stroke depression experience a lower degree of social participation. Depression explains 51% of the decline in participation following a stroke. The present findings can serve as a basis to assist he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, the relationship between post stroke depression and functional outcome after stroke is not well understood [45]. Previous studies on self-perceived participation and depression after stroke have shown that depression/depressive moods were associated with restricted participation in various life areas [10, 14, 17, 37, 47]. In terms of the IPA, depressive mood [17] was an explanatory factor associated with restrictions in all the domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between post stroke depression and functional outcome after stroke is not well understood [45]. Previous studies on self-perceived participation and depression after stroke have shown that depression/depressive moods were associated with restricted participation in various life areas [10, 14, 17, 37, 47]. In terms of the IPA, depressive mood [17] was an explanatory factor associated with restrictions in all the domains.…”
Section: Discussionmentioning
confidence: 99%
“…17% reported taking medication for their feelings of depression, which is in line with the reported prevalence of depression which ranges from 19% to 33% (Hackett, Yapa, Parag, & Anderson, ; Robinson, ). No studies were found about association between depression and occupational gaps, but depression has been identified as a negative factor for participation after stroke (D'Alisa, Baudo, Mauro, & Miscio, ; Micaela Silva et al., ), which strengthens the findings of association between depression and occupational gaps after stroke.…”
Section: Discussionmentioning
confidence: 61%
“…However, the presence of depression was associated with significantly more restriction in participation as assessed by the Participation Scale in cases of depressed patients with schizophrenia as compared to non-depressed individuals, which is a well-established fact that depression and social participation are inversely related (Micaela Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%